The behaviour of resin-bond diamond wheels in the grinding of advanced ceramics - Bianchi, Eduardo Carlos [UNESP]; Da Silva, Eraldo Jannone [UNESP]; Da Silva, Carlos Elias; De Souza, Galdino Ferreira; Fortulan, Carlos Alberto; Fernandes, Odilson Coimbra [UNESP]; Valarelli, Ivan de Domenico [UNESP]; Aguiar, Paulo Roberto [UNESP] (My University, 1998)
Results are reported of the behaviour of the plane tangential grinding process using diamond grinding wheels. Grinding performance is analysed in terms of the wear behaviour of the wheel in the grinding of ceramic. Discussion of the results concentrates on the wear mechanism of the diamond wheel and the process of material removal.